(untitled) (The International Journal for Scientific Research, 2024)
Introduction: Humanized anti-VEGF (Vascular endothelial growth factor) antibody fragment Lucentis (Ranibizumab) is prescribed to treat neovascular (wet) age-related macular degeneration, diabetic macular edema, diabetic retinopathy, and myopic choroidal neovascularization. It is also used to treat macular edema following retinal vein occlusion. Objective: This study was carried out to evaluate the anatomic effect and visual acuity response following intravitreal Lucentis (Ranibizumab). Methodology: In this investigation, diffuse diabetic macular edema was present in 30 eyes belonging to 30 patients with stable diabetes mellitus. Every eye had undergone argon laser photocoagulation, either Focal, Grid, or pan-retinal photocoagulation (PRP), for a minimum of three months. The patients with a mean age was 58.13±5.17 years were treated with two intravitreal injections of 0.5 mg of ranibizumab in 0.05 ml spaced four weeks apart. A skilled ophthalmologist assessed each patient’s best-corrected visual acuity (BCVA), also assessed their central macular thickness (CMT) using optical coherence tomography, and assessed their diabetic retinopathy at both the baseline and follow-up sessions. The results: The results showed that the means of BCVA were significantly (P<0.01) decreased from baseline (1.189±0.077 logMAR) to 1 month (0.162±0.058 logMAR) and 3 months (1.109±0.049 logMAR) after injection. Also the results revealed that the mean of CMT were significantly (P<0.01) declined from the baseline (477.47±151.32 µm) to 1 month (438.27±115.68 µm) and 3 month (396.80±115.26 µm) after treatment. Conclusions: The study concluded that after three months of the second injection of Lucentis (ranibizumab) significantly reduced central macular thickness and improved visual acuity, then diffuse diabetic macular edema is significantly improved and treated using Lucentis (ranibizumab).